Veneno como narrativa emergente de las plataformas de streaming y el renacimiento de un ícono de la comunidad LGBTI: Series de televisión como protagonistas del surgimiento y las memorias de personajes dentro de las narrativas audiovisuales (Monográfico) - Vega Reyes, Jorge Andrés (2022)
Veneno is a Spanish series created by Javier Calvo and Javier Ambrossi, and narrates the life of Cristina Ortiz, la Veneno; It is a biopic based on the work “I say! Neither whore nor saint: The memories of La Veneno”, written by Valeria Vega. The series was realeased on the Atresplayer Premium and HBO Max platforms. Cristina was an actress, celebrity, model, sex worker and star, she was one of the first women to make the trans community visible In Spain. This article takes the Veneno series to analyze its influence and example of how, through emerging narratives, they position and reborn iconic characters of the LGBTI community. This is the case of Cristina Ortiz, la Veneno, who was a visible icon of the trans community in the nineties on Spanish television, and who, thanks to the series, had a rebirth and visibility in the new generations, who knew her history thanks to streaming platforms. Likewise, an approach is made to the main films and series that address the transsexual theme and also the inclusion of trans characters, marking a before and after since the arrival of streaming platforms and how the series Veneno has managed to make visible the trans thematic in a transcendental way.